Fundamental characterization of lubrication effects through various cooling lubricants in the chip formation zone - Biermann, Dirk; Saelzer, Jannis; Bergmann, Benjamin; Schenzel, Jan; Menze, Christian J.; Gerken, Julian Frederic; Wolf, Tobias; Denkena, Berend; Möhring, Hans-Christian; Zabel, Andreas (Springer Science and Business Media LLC, 2024)
Using cooling lubricants in metalworking requires a high consumption of energy and resources. However, cooling lubricants serve to increase the productivity and quality of these processes. Accordingly, it is necessary to expand the efficiency of their application. This requires fundamental understanding of the working mechanisms. Driven by this motivation, this publication compares six cooling lubricants regarding their lubrication effect in orthogonal cutting. Three types of fluid supply, each conducted on a specific special machine tool for chip formation analysis, and two cutting speeds have been used in the tests. In order to analyze the lubricating effect of these different scenarios, force measurements were carried out and the chip formation was recorded with high-speed recordings. It was found that the process improvements due to lubrication is determined by the interaction of fluid properties, supply strategy and cutting speed. Moreover, clear limitations of water-based cooling lubricants (especially oil-water-emulsions) in the ability to lubricate the chip formation zone have been determined and quantified.
Production engineering; 19(1)
Keywords: Cutting; Chip formation; Tribology; Friction; Lubrication; 620; 670; Spanende Bearbeitung; Spanbildung; Tribologie; Reibung; Schmierung